Pengaruh Faktor Internal dan Faktor Eksternal Terhadap Nilai Perusahaan - Sukma Prasitadewi, Made; Wijana Asmara Putra, I Nyoman (E-Jurnal Akuntansi; Vol 30 No 6 (2020)DO - 10.24843/EJA.2020.v30.i06.p05, 2020)
The purpose of this study was to determine the effect of profitability, dividend policy, funding decisions, inflation, interest rates and currency exchange rates. This study took a sample of manufacturing companies listed on the Indonesia Stock Exchange in the period 2016-2018. The technique used in this research is multiple linear regression analysis. based on the results of the analysis of this study proves that profitability has a positive effect on firm value. Dividend policy does not affect the value of the company. Funding decisions negatively affect the value of the company. Inflation has a negative effect on firm value. Interest rates have a negative effect on firm value. Currency exchange rates have a negative effect on company value. Keywords: Profitability; Dividend Policy; Funding Decision; Inflation; Interest Rates; Currency Exchange Rates.